Comparison of growth characteristics between the indigenous Oreochromis andersonii and the domesticated Oreochromis niloticus under experimental conditions - Wegener, Anthony Marc (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.